2014
DOI: 10.1093/alcalc/agu094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microelement Concentration on the Intensity of Alcohol Withdrawal Syndrome

Abstract: Evidence from literature and our experiment suggests that brain activity, especially the glutamatergic system, might be directly involved in micronutrient concentrations. Therefore, their supplementation to the AWS patient might improve symptom evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
2
Order By: Relevance
“…The optimal safe dose for human pregnancy needs to be clinically defined. The association of alcohol during embryonic exposure with elevated HCy levels and FA prevention (Han et al, ; Serrano et al, ) has been confirmed since then by multiple studies in the alcohol literature (Shirpoor et al, ; Kharbanda et al, ; Kruman and Fowler, ; Prior et al, ). It appears that folate deficiency is associated with the observed dyslipidemia in the fetus and placenta from a binge level of alcohol exposure.…”
Section: Discussionmentioning
confidence: 89%
“…The optimal safe dose for human pregnancy needs to be clinically defined. The association of alcohol during embryonic exposure with elevated HCy levels and FA prevention (Han et al, ; Serrano et al, ) has been confirmed since then by multiple studies in the alcohol literature (Shirpoor et al, ; Kharbanda et al, ; Kruman and Fowler, ; Prior et al, ). It appears that folate deficiency is associated with the observed dyslipidemia in the fetus and placenta from a binge level of alcohol exposure.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, in a study we developed, we observed a direct association between lower plasmatic levels of zinc and magnesium and greater intensity of AWS symptoms [17].…”
mentioning
confidence: 78%
“…The anorectic influence of alcohol on the satiety centers of the hypothalamus leads alcoholic abusers to refuse food. Furthermore, alcoholic patients lack adequate nutrition in their diet and attempt to meet their caloric needs from ethanol consumption leading to alcoholics being hungry many days while drinking heavily 27,28,33 .…”
Section: Discussionmentioning
confidence: 99%